Aspects of Platonic Eros in Symposium and Phaedrus - Stamos, Fotis (Conatus - Journal of Philosophy, 2017)
The platonic Love [Eros]; a matter that raised and keeps raising still thoughts and talks; a crucial matter for Plato himself. But what really is it? To whom or what does it turn to; What is this that it intends for? Guided by Plato’s work itself, and especially by Symposium and the first part of the extensive Phaidros, I intend to bring to the surface the most crucial views of platonic Love. Through the successive speeches in Symposium; through the many encomiums made by each and everyone of Socrates speakers, in the end, the philosopher does not simply speak about Love, but he discloses it. Same goes in Phaidros; had the speech contests taken place between Socrates and Lysias, the philosopher, had his face uncovered – through his first speech Socrates had his face covered in order not to commit hubris –, tergiversates and reveals that furious state to its whole. Three will be the main points the following paper will try to expound: i) What is the so named platonic Love? ii) What does the lover desire to conquer? iii) How does Plato speaks to us about it through his work?